Super-resolution microscopy reveals glioma cell footprints and exosome deposits - Stefania Petrini; Frédéric Eghiaian; Valentina Apollonio; Giulia Pericoli; Maria Vinci (Cell Adhesion & Migration, 2025)
Gliomas are aggressive brain tumors whose infiltrative growth is mediated by intercellular crosstalk. Exosomes, small extracellular vesicles, play a key role in cell–cell communication but are difficult to visualize using conventional microscopy. Performing immunostaining for CD63, a known exosome marker, and using STED microscopy, we demonstrate exosome secretion in primary glioma cells. Applying mathematical deconvolution, we enhance the contrast and resolution for in-depth analysis of STED images. We identify CD63-positive cellular footprints and exosome deposits in the extracellular space. Quantitative analysis shows CD63-positive exosomes ranging 36.55-157.06 nm in size. CD63/actin co-staining demonstrates different actin polymerization states associated with exosomes. In conclusion, STED microscopy coupled with immunostaining allows exosome primary characterization at the single-vesicle level in the cellular spatial context.